SAT0045 Dna methylation of socs3 as a possible mechanism for persistent urate induced inflammation. (12th June 2018) - Klück, V.; Crisan, T.; Cleophas, M.; Keating, S.; Novakovic, B.; Dalbeth, N.; Stamp, L.; Phipps-Green, A.; Black, M.; Macartney-Coxson, D.; Merriman, T.; Joosten, L.
Abstract : Background: Hyperuricemia is a metabolic condition associated with cardiovascular diseases. 1 However, mechanisms for a causal relation have not been fully elucidated yet. Previously, we showed that monocytes primed with urate show a shift in the balance of cytokine production: increased proinflammatory cytokines and decreased levels of IL-1 receptor antagonist. 2 Objectives: In this study we investigate if these changes to urate exposure are persistent and whether changes in DNA methylation serve as a molecular substrate for these effects of hyperuricemia. Methods: DNA methylation was assessed in whole blood of 80 individuals of Maori ancestry with varying serumurate levels. Human PBMCs and monocytes from Dutch healthy volunteers were isolated and pretreated for 24 hour with urate. Cells were either directly stimulated with LPS or LPS/MSU or subjected to increasing resting days before restimulation. Cytokine levels were determined in supernatants by ELISA. SOCS3 mRNA levels were determined by qPCR after 24 hour urate priming. Phosphorylation of STAT3 was assessed after stimulation by flow cytometry with intracellular staining for pSTAT3. Results: Human PBMCs primed with urate demonstrated increased IL-1β and IL-6 responses and decreased IL-1Ra production compared to controls. Although IL-1β production was diminished after increasing resting days, persistent effects were observed for the reduction of IL-1Ra and induction of IL-6. To investigate whether these persistent changes were mediated by epigenetic changes, differences in DNA methylation between normouricemic and hyperuricemic individuals were assessed. SOCS3 gene was higher methylated at 3 neighbouring SOCS3 intragenic positions in hyperuricemic individuals. In vitro, SOCS3 mRNA levels were significantly increased in monocytes after 24 hour urate treatment. Moreover, urate dose-dependently suppressed the phosphorylation of STAT3 after stimulation. Conclusions: In this study we demonstrated that urate has persistent proinflammatory effects on human monocytes. Higher SOCS3 DNA methylation is observed in hyperuricemic individuals. In vitro, urate priming leads to increased levels of SOCS3 mRNA and consequently suppression of STAT3 phosphorylation. Interestingly, STAT3 inhibition has been reported to mediate IL-1Ra downregulation. 3 Therefore, we hypothesize urate induced inflammation is at least partly mediated by changes in methylation of the SOCS3 gene. However, further validation of this pathway is needed to elucidate possible targets for therapy. REFERENCES: [1] Soltani Z, et al. Potential role of urate in metabolic syndrome, hypertension, kidney injury, and cardiovascular diseases: is it time for reappraisal?. Ann Rheum Dis2016;75(4):755–62. [2] Crisan TO, et al. Soluble urate primes TLR-induced proinflammatory cytokine production by human primary cells via inhibition of IL-1Ra. Ann Rheum Dis2016;75(4):755–62. [3] Tamassia N, et al. Uncovering an IL-10-dependent NF-kappaB recruitment to the IL-1ra promoter that is impaired in STAT3 functionally defective patients. Faseb j2010;24(5):1365–75. Disclosure of Interest: None declared